Balancing stakeholder interests: A Balanced Scorecard perspective on performance appraisal implementation in China's public hospitals - Yao, S.; Ma, S.; Shi, L.; Wu, F.; Reis, E. (International Journal of Health Planning and Management, 2025)
In 2019, the Chinese government initiated a National Performance Appraisal for Tertiary Public Hospitals (the ‘National Appraisal’), but limited study has been conducted on its appraisal indicators and its implementation effects. This study aims to assess how well this system balances the interests of key stakeholders in Chinese public hospitals and examines the positive changes and concurrent challenges it has brought to hospital operations. Utilising stakeholder theory and the balanced scorecard, we conducted two rounds of Delphi consultations with experts (N1 = 46, N2 = 29). We also analysed archival data from three hospitals' ‘National Appraisal’ records covering 2018 to 2020. Additionally, we conducted semi-structured interviews (N = 41) with key stakeholders from these hospitals. Kendall's coefficient of concordance was employed in both rounds to gauge the agreement among experts and thematic analysis was applied to analyse data from in-depth interviews with the key stakeholders of the three sampled hospitals. The results show that: (1) The key stakeholders of Chinese public hospitals include patients, hospital executives, health care workers, health authorities, and the public, but the ‘National Appraisal’ indicators only cover the first three stakeholders; (2) The ‘National Appraisal’ system adopted a balanced scorecard approach, patient-centre and with emphases on internal process; (3) The ‘National Appraisal’ had positive impacts on hospitals, clarifying hospital strategy and prioritising the public roles, enhancing health care quality, safety, and efficiency, as well as patient and health care worker satisfaction. However, implementation challenges arise from resource constraints, discrepancy between appraisal indicators and patient needs, misalignment between appraisal indicators and doctor's patient care practices, and the tension between nationwide standardized appraisal and local context. This study significantly contributes to the literature by empirically examining performance appraisal implementation in an under-researched country's public hospitals, offering practical implications and policy recommendations for practitioners, managers, and policymakers.